2021
DOI: 10.3390/cells10102535
|View full text |Cite
|
Sign up to set email alerts
|

How Viruses Hijack and Modify the Secretory Transport Pathway

Abstract: Eukaryotic cells contain dynamic membrane-bound organelles that are constantly remodeled in response to physiological and environmental cues. Key organelles are the endoplasmic reticulum, the Golgi apparatus and the plasma membrane, which are interconnected by vesicular traffic through the secretory transport route. Numerous viruses, especially enveloped viruses, use and modify compartments of the secretory pathway to promote their replication, assembly and cell egression by hijacking the host cell machinery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 180 publications
(480 reference statements)
0
13
0
Order By: Relevance
“…Viruses hijack the cell membrane machinery for their entry. [ 49–51 ] Interestingly, we found that the actin filament‐exerted tensile force of cell membrane that regulates the mobility of cell membrane was significantly reduced in various Lyz2 ‐Cre; Trpv2 fl/fl myeloid cells compared to the Trpv2 fl/fl counterparts. Such a process is dependent on the homeostatic Ca 2+ influx mediated by TRPV channels, as reconstitution of TRPV1 or TRPV2 but not TRPV2 E572Q or TRPV1 D646N/E648/651Q into Lyz2 ‐Cre; Trpv2 fl/fl BMDCs restored the membrane tension.…”
Section: Discussionmentioning
confidence: 93%
“…Viruses hijack the cell membrane machinery for their entry. [ 49–51 ] Interestingly, we found that the actin filament‐exerted tensile force of cell membrane that regulates the mobility of cell membrane was significantly reduced in various Lyz2 ‐Cre; Trpv2 fl/fl myeloid cells compared to the Trpv2 fl/fl counterparts. Such a process is dependent on the homeostatic Ca 2+ influx mediated by TRPV channels, as reconstitution of TRPV1 or TRPV2 but not TRPV2 E572Q or TRPV1 D646N/E648/651Q into Lyz2 ‐Cre; Trpv2 fl/fl BMDCs restored the membrane tension.…”
Section: Discussionmentioning
confidence: 93%
“…These network-based results also support previous studies that have shown how SARS-CoV-2 hijacks the rough endoplasmic reticulum (RER)-linked host translational machinery for its replication [ 11 ]. In addition, NIP targets were enriched for pathways related to protein export ( P = 8.99 × 10 −5 ), which also includes secretory pathways that are hijacked by the virus to carry out their essential functions, such as virus replication, assembly and egress, demonstrating that viruses evade host cellular pathways to promote their propagation [ 25 ]. These results indicate that the extended target set consisting of the top-200 NIPs identified by the RWR algorithm do not only populate similar pathways as VIPs but are also implicated in various biological processes related to viral infection.…”
Section: Resultsmentioning
confidence: 99%
“…These network-based results also support previous studies that have shown how SARS-CoV-2 hijacks the rough endoplasmic reticulum (RER)-linked host translational machinery for its replication (11,30). In addition, NIP proteins were enriched for pathways related to protein export (P=8.99×10 −5 ), which also includes secretory pathways that are hijacked by the virus to carry out their essential functions, such as virus replication, assembly, and egress, demonstrating that viruses evade host cellular pathways to promote their propagation (25). These results indicate that the extended target set consisting of the top-200 NIP host proteins identified by the RWR algorithm not only populate similar pathways as VIPs but are also implicated in various biological processes related to viral infection.…”
Section: Resultsmentioning
confidence: 99%